2018
DOI: 10.1155/2018/9579348
|View full text |Cite
|
Sign up to set email alerts
|

Low Carbon Distribution Channel Coordination with a Capital-Constrained Retailer

Abstract: Capital constraints exist in many supply chains. We examine a low carbon distribution channel that consists of a manufacturer and a retailer, in which the retailer is constrained by capital. The retailer can be financed by bank credit from a competitive bank market. A Stackelberg model is developed to analyze the integrated decision-making process of ordering, financing, and emission reduction. By comparing the decentralized and centralized channels, we obtain that the manufacturer's green technology investmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 38 publications
0
1
0
1
Order By: Relevance
“…e authors conducted empirical research on the pilot emissions trading mechanism in Hubei, China, to explore the effect of carbon quota constraints. Wang, Cheng, and Zhang [27] pointed out that the emission trading mechanism is more flexibility and cost-effectiveness and can become a common way to achieve emission reduction targets. Peng, Pang, and Cong [28] and Xu, Wang, and Zhao [29] improved revenue sharing contracts that can coordinate supply chains via emission reduction subsidy and cost-sharing mechanisms, respectively.…”
Section: Low-carbon Supply Chainsmentioning
confidence: 99%
See 2 more Smart Citations
“…e authors conducted empirical research on the pilot emissions trading mechanism in Hubei, China, to explore the effect of carbon quota constraints. Wang, Cheng, and Zhang [27] pointed out that the emission trading mechanism is more flexibility and cost-effectiveness and can become a common way to achieve emission reduction targets. Peng, Pang, and Cong [28] and Xu, Wang, and Zhao [29] improved revenue sharing contracts that can coordinate supply chains via emission reduction subsidy and cost-sharing mechanisms, respectively.…”
Section: Low-carbon Supply Chainsmentioning
confidence: 99%
“…For instance, Wang, Yu, and Jin [41] pointed out that capital constraints are an important factor that restricts the development of SME e-commerce platforms. Wang, Cheng, and Zhang [27] showed that bank credit can enhance the overall efficiency of the supply chain with a SME retailer and achieve Pareto improvement for both supply chain members via a functional revenue sharing contract. Considering two retailers with limited capital, Yang, Miao, and Zhao [42] examined the impact of credit strategy on green supply chain performance.…”
Section: Supply Chain Financementioning
confidence: 99%
See 1 more Smart Citation
“…It has now been widely recognized that the Earth's limited natural resources and assimilation capacity are unsustainable in the face of increased global development [11,40,41]. Production mode must be changed to achieve a sustainable economy [42]. One of the most considered environmental objectives has been the minimization of emissions that negatively impact human health and climate [43,44].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Entre estes modelos analíticos que demandam dados mais focados, é possível observar que o tema ambiental é frequentemente relacionado a questões associadas à emissão de gases do efeito estufa, tanto por parte da empresa quanto por parte dos demais agentes da cadeia (e.g., Awad & Hassan, 2018;Darom et al, 2018;Wang et al, 2018;Matar & Elshurafa, 2017;Ben-Salem et al, 2016;Jain et al, 2016;Hugo et al, 2005). Eles exploram métodos multicritérios de decisão voltados, por exemplo, ao mercado de carbono, regulamentações (principalmente quando são estabelecidos limites de emissão) e custos associados às emissões, utilizando-se métodos matemáticos de otimização.…”
Section: Classificaçõesunclassified